2019
DOI: 10.18280/ts.360603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the EEG Signals and Eye Tracker Data for Working Different N-Back Modes

Abstract: In this study, it is aimed to determine the effects of different modes N-back test which is one of the measurement tools frequently used in measurement of working memory, on the Electroencephalography (EEG) and Eye-tracker data. Eight healthy volunteers participated in this study. The volunteers performed tasks inducing stress and mental fatigue for almost 4 minutes. Each experimental task consists of 72-seconds stress and fatigue inducing 1-position back, 2-position-color and 2-position-image test sessions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For example, we have incorporated time constraints and performance feedback to further enhance the stress response. Previous studies [ 13 , 14 ] have demonstrated the effectiveness of the tests in inducing stress.…”
Section: Data Collection Paradigms and Schemesmentioning
confidence: 99%
“…For example, we have incorporated time constraints and performance feedback to further enhance the stress response. Previous studies [ 13 , 14 ] have demonstrated the effectiveness of the tests in inducing stress.…”
Section: Data Collection Paradigms and Schemesmentioning
confidence: 99%